Deaths in police custody. (July 2018) - Heide, Steffen; Chan, Theodore
Abstract: Deaths in police custody often attract a huge amount of public interest and are frequently associated with controversy related to causation. While systematic investigations of deaths in police custody are currently available for countries in Europe, North America and Australia, the different inclusion and exclusion criteria and the lack of a uniform definition limits their comparability. Rates of death vary by age and gender with some similarities across different countries and continents. The male dominance is essentially due to the fact that around the world women are much less frequently taken into police custody than men. Similarly, in the U.S., the most common cause of custody death was natural illness and disease progression such as heart disease and cancer; along with high rates of suicide deaths. In most European countries there is a considerable dominance of non-natural deaths. The causes of death are dominated by alcohol, drugs and medications, but suicide, injury and trauma are also common. Deaths in custody require careful investigation to determine causality as well as culpability when appropriate. While many deaths may not be preventable, some are. Further systematic research of this issue, including detailed analyses and investigations of such cases, is necessary to develop general and specific preventative measures to reduce the risk of death in the custody population. Highlights: Deaths in police custody often attract a huge amount of public interest. We analyse systematic investigations of deaths in police custody. In the U.S. the most common cause of custody death was natural illness. In most European countries there is a considerable dominance of non-natural deaths. Further systematic research of this issue is necessary.